CAN THE PROJECTS OF CALATRAVA BE SIMULACRAS OF A CONTEMPORARY ARCHITECTURE SIMULATION? - Sagdic, Zafer (STEF92 TECHNOLOGY LTD, 2014)
While thinking on and writing on the contemporary architecture of 21st century, it is known that there are always encounters difficulties and restrictiveness of making distinct descriptions, because of the existence of many different interesting architectural project examples all over the world. All kinds of descriptive approaches to be held towards the field of contemporary architecture and/or the names that are producing works in the field will inevitably include some details while they also will exclude some other values and details of these projects. Each and every description is attempted to be put forward about these projects will somehow define a power and include invariability from the point of view of the writer. In this context, while this paper contains some ideas about Calatrava, one of the star architectures of 21st century in the practice of architecture, it will not include limited descriptions and/or it will not attempt to bring some current common knowledge about him to some extent. Also with the awareness of the fact that each architectural product that is included and produced within production practice, contains its own paradigms, this paper will not include an idea of the fact that structures of Calatrava are only virtually important for the field on the contrary of the common idea in the field. However, the paper will try to show the relationship between the theorem called Simulacra and Simulations of Jean Baudrillard and the projects of Calatrava, especially mentioned on his project known as La Cuidad de Las Artes y de Las Ciencias. While the paper will be mention the paradigms that are formulating his architectural point of view, also it will attempt to reflect an intuitive point of view about a star architect of the 21st century, who combines several sub-components of arts and architectural practice and who performs them all together. It seems that the story of Calatrava, from the first days on the praxis till today is based on a direct relationship between the existence of the capital on neo- liberal economies and the newborn trend of searching an extravaganza in the praxis. Thus, the paper will discuss the question of can creating of simulacras on architecture posibble? on Calatrava's projects.
Keywords: Calatrava; architecture; simulacra; simulation; Baudrillard; Arts & Humanities - Other Topics